The vanquished : why the First World War failed to end - Gerwarth, Robert (Farrar, Straus and Giroux, 2016)
"An epic, groundbreaking account of the ethnic and state violence that followed the end of World War I-- conflicts that would shape the course of the twentieth century. For the Western allies, November 11, 1918 has always been a solemn date-- the end of fighting that had destroyed a generation, but also a vindication of a terrible sacrifice with the total collapse of the principal enemies: the German Empire, Austria-Hungary, and the Ottoman Empire. But for much of the rest of Europe this was a day with no meaning, as a continuing, nightmarish series of conflicts engulfed country after country. In The Vanquished, a highly original and gripping work of history, Robert Gerwarth asks us to think again about the true legacy of the First World War. In large part it was not the fighting on the Western Front that proved so ruinous to Europe's future, but the devastating aftermath, as countries on both sides of the original conflict were savaged by revolutions, pogroms, mass expulsions, and further major military clashes. If the war itself had in most places been a struggle mainly between state-backed soldiers, these new conflicts were predominantly perpetrated by civilians and paramilitaries, and driven by a murderous sense of injustice projected on to enemies real and imaginary. In the years immediately after the armistice, millions would die across Central, Eastern, and Southeastern Europe before the Soviet Union and a series of rickety and exhausted small new states would come into being. It was here, in the ruins of Europe, that extreme ideologies such as fascism would take shape and ultimately emerge triumphant in Italy, Germany, and elsewhere. As absorbing in its drama as it is unsettling in its analysis, The Vanquished is destined to transform our understanding of not just the First World War but of the twentieth century as a whole"--Provided by publisher.